Lucas numbers of the form PX2, where P is prime - Neville Robbins (International Journal of Mathematics and Mathematical Sciences)
Let Ln denote the nth Lucas number, where n is a natural number. Using elementary techniques, we find all solutions of the equation: Ln=px2 where p is prime and p<1000.